2019
DOI: 10.2147/dmso.s233717
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Association Between Prediabetes and Dyslipidemia Among Attendants of Primary Care Health Centers in Jeddah, Saudi Arabia</p>

Abstract: Introduction: Early detection and treatment of dysglycemia including diabetes and prediabetes is demonstrated to improve disease outcomes and prevent complications. Objective: To assess the association of prediabetes with lipid metabolism disorders to clarify whether systematic screening for prediabetes should be proposed for individuals with dyslipidemia. Material and Methods: A cross-sectional study design, employing a stratified two-stage cluster sampling method recruited non-diabetic adults (age ≥18 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 45 publications
5
17
0
6
Order By: Relevance
“…The prevalence of high TG in the current study was lower than previously reported [ 11 ] being 11.4% for young adults aged 30 years or under compared to with 32% in the older adults aged more than 30 years. This difference in prevalence is due to the variation in the cut-off point to determine hypertriglyceridemia as it was ≥ 1.7 mmol/L in our study as well as in that of Al-Amri et al [ 32 ] whereas ≥ 1.27 mmol/L was adopted in the previous study [ 11 ]. The cut-off point in this previous study allowed a wider range of the population to be diagnosed with hypertriglyceridemia, and therefore a higher prevalence was reported.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The prevalence of high TG in the current study was lower than previously reported [ 11 ] being 11.4% for young adults aged 30 years or under compared to with 32% in the older adults aged more than 30 years. This difference in prevalence is due to the variation in the cut-off point to determine hypertriglyceridemia as it was ≥ 1.7 mmol/L in our study as well as in that of Al-Amri et al [ 32 ] whereas ≥ 1.27 mmol/L was adopted in the previous study [ 11 ]. The cut-off point in this previous study allowed a wider range of the population to be diagnosed with hypertriglyceridemia, and therefore a higher prevalence was reported.…”
Section: Discussionmentioning
confidence: 74%
“…Cinnamon drink is commonly ingested by Saudi individuals who are diagnosed with dysglycemia due to the common belief that cinnamon lowers blood sugar. Since dysglycemia occurs more in individuals with dyslipidemia particularly high LDL-C [ 32 ], changes in dietary habits such as increasing consumption of cinnamon drink or fresh vegetables in individuals diagnosed with dysglycemia or dyslipidemia can result in biased observations regarding the effect of these food types on serum lipids. In order to obtain a clear picture, future studies should include information on the duration of the recorded dietary habits, and whether dietary practices have been changed due to medical advice.…”
Section: Discussionmentioning
confidence: 99%
“…В ходе когортных исследований получена информация о распространенности предиабета среди населения (табл. 1 [6][7][8][9][10][11][12][13][14]), однако, оценки варьируются в зависимости от порогов, используемых в диагностики предиабета, и основных характеристик населения [4,5]. Недавние исследования, проведенные в США и Великобритании, указывают на то, что распространенность предиабета у взрослых составляет 38% и 35% соответственно [5].…”
Section: эпидемиология и прогнозunclassified
“…Breyer M.K., Ofenheimer A., Altziebler J. et al, 2020 [13] Обсервационное популяционное когортное исследование 11014 пациентов, Швеция Observational population cohort study of 11014 patients, Sweden Распространенность предиабета составляла 20,2% (мужчины -23,6%; женщины -17,1%) The prevalence of prediabetes was 20,2% (men -23,6%; women -17,1%) Al Amri T., Bahijri S., Al-Raddadi R. et al, 2019 [14] Перекрестное исследование, стратифицированный двухэтапный метод кластерной выборки, взрослые без диабета ≥18 лет из посетителей центров первичной медико-санитарной помощи в Джидде Cross-sectional study, stratified two-stage cluster sampling method, adults without diabetes ≥18 years of age from visitors to primary health care centers in Jeddah Включено 613 человек, 32±11,8 года, из которых 54,8% составляли женщины. Предиабет выявлен у 28,7% It included 613 people, 32±11,8 years, of which 54,8% were women.…”
Section: эпидемиология и прогнозunclassified
See 1 more Smart Citation